Molecules to Ecosystems: Actinomycete Natural Products In situ - Behie, Scott W.; Bonet, Bailey; Zacharia, Vineetha M.; McClung, Dylan J.; Traxler, Matthew F. (Frontiers in Microbiology, 2017)
Actinomycetes, filamentous actinobacteria found in numerous ecosystems around the globe, produce a wide range of clinically useful natural products. In natural environments, actinomycetes live in dynamic communities where environmental cues and ecological interactions likely influence natural product biosynthesis. Our current understating of these cues, and the ecological roles of natural products, is in its infancy. We postulate that understanding the ecological context in which actinomycete metabolites are made is fundamental to advancing the discovery of novel natural products. In this review we explore the ecological relevance of actinomycetes and their secondary metabolites from varying ecosystems, and suggest that investigating the ecology of actinomycete interactions warrants particular attention with respect to metabolite discovery. Furthermore, we focus on the chemical ecology and in situ analysis of actinomycete natural products and consider the implications for natural product biosynthesis at ecosystem scales.